Polycarbonate Microchip Containing CuBTC-Monopol Monolith for Solid-Phase Extraction of Dyes - Eman Alzahrani (International Journal of Analytical Chemistry)
In the present study, preparation of CuBTC-monopol monoliths for use within the microchip solid phase extraction was undertaken through a 20-min UV lamp-assisted polymerization for 2,2-dimethoxy-2-phenyl acetophenone (DMPA), butyl methacrylate (BMA), and ethylene dimethacrylate (EDMA) alongside inclusion of the porogenic solvent system (1-propanol and methanol (1 : 1)). The resultant coating underwent coating using CuBTC nanocrystals in ethanolic solution of ethanolic solution of 1,3,5-benzenetricarboxylic acid (H3BTC, 10 mM) and 10 mM copper(II) acetate Cu(CH3COO)2. This paper reports enhanced extraction, characterization, and synthesis studies for porous CuBTC metal organic frameworks that are marked by different methods including SEM/EDAX analysis, atomic force microscopy (AFM), and Fourier-transform infrared spectroscopy (FT-IR). The evaluation of the microchip’s performance was undertaken as sorbent through retrieval of six toxic dyes (anionic and cationic dyes). Various parameters (desorption and extraction step flow rates, volume of desorption solvent, volume of sample, and type of desorption solvent) were examined to optimize dye extraction using fabricated microchips. The result indicated that CuBTC-monopol monoliths were permeable with the ability of removing impurities and attained high toxic dye extraction recovery (83.4–99.9%). The assessment of reproducibility for chip-to-chip was undertaken by computing the relative standard deviations (RSDs) of the six dyes in extraction. The interbatch and intrabatch RSDs ranged between 3.8 and 6.9% and 2.3 and 4.8%. Such features showed that fabricated CuBTC-monopol monolithic disk polycarbonate microchips have the potential of extracting toxic dyes that could be utilized for treating wastewater.